Cheese whey as potential medium fermentation to Saccharomyces fragilis IZ 275 yeast - Bosso, Alessandra; Bosso Tomal, Adriana Aparecida; Caldeirão, Lucas; da Silva, Josemeyre Bonifácio; Suguimoto, Hélio Hiroshi (Scientia Plena, 2020)
Yeasts β-galactosidase is intracellular enzyme, show a high lactose hydrolyzing capacity and therefore can be used to reduce the level of lactose of milk and dairy products. However, the activity of β-galactosidase, or its production, is strongly influenced by carbon availability as source of energy. The aim of this work was to compare different carbons source with the cheese whey, by-product of dairy industry and potential source to grow microorganism, and its interactions as fermentation mediums to production maximum of β-galactosidase by Saccharomyces fragilis IZ 275 yeast. The enzymatic activity in the cheese whey and others carbon sources were determined using the o-nitrophenyl-β-D-galactopyranoside substrate (ONPG). The cheese whey is the better medium fermentation, when compared with others carbon sources, to the production maximum of enzyme. Thus, considered as waste by industry, we prove that the cheese whey opens up another possibility of biotechnological use adding value to the byproduct and meeting the concept of bioeconomy or circular economy.